Study the incidence of complications of BCG vaccine in infants of Babol, Mazandaran (2011-2013) - Rahim Barari-Savadkoohi; Azin Shour; Jila Masrour-Roudsari (Babol University of Medical Sciences, 2016)
Background: BCG vaccination which is administered to prevent tuberculosis is sometimes associated with serious complications. This study aimed to determine the incidence of complications of BCG vaccination in Babol. Methods: All infants who received BCG vaccination between 2011-2013 in health centers of Babol entered the study. Data regarding complications of vaccine were extracted according to the National Inventory of babies. All complicated cases were confirmed by the Academic Committee to review the adverse consequences of the vaccine. Results: Among the 15984 vaccinated neonates, 150 (0.93%) cases presented lymphadenitis. 46.5% were females and 53.5% were males 43% were rural residents and 57% were urban residents. No cases of lymphadenitis including 1% of lymphadenitis with abscess formation were recovered without treatment. Disseminated infection occurred in 3 cases of immune deficient patients who responded to the treatment. Most complications occurred during 4 months after vaccination. Conclusion: According to the results of this study, the prevalence of lymphadenitis in Babol was higher than the standard of WHO. This may be attributed to type and vaccine storage and injection technique. These findings justify further training of health-center workers.